(untitled) (Journal of Hama University, 2026)
Abstract Given the importance of the detecting of the differential item functioning, that the existence of it threatens the fairness of the test, and in light of the multiplicity of methods used to detect it, the current research aimed to compare the Mantel-Haenszel and logistic regression methods in detecting the differential item functioning. To achieve this goal, the Social Phobia Scale prepared by Rollin and Wei, consisting of (36) items, was applied to a sample of students from the Faculties of Education and Economics at Tartous University, consisting of (686) male and female students, (410) females and (276) males. The statistical processing was done using the (difR) package, and the results showed the following: 1- The Mantel-Haenszel method identified (7) items with differential item functioning for gender out of (36) items for the social phobia scale, while the logistic regression method identified (12) items, and there was agreement between the two methods in identifying (5) items. 2- The effect sizes of differential functioning of items identified by the Mantel-Haenszel method ranged from moderate to large, while all effect sizes of differential functioning of items identified by the logistic regression method were small. 3- The preferences of items with differential functioning were distributed between males and females according to the Mantel-Haenszel and logistic regression methods, and the preferences of items shared between the two methods were distributed similarly between males and females.